Eficiência dos municípios com relação aos gastos públicos na microrregião de Varginha/MG - Ázara, Leiziane Neves De (2016)
Studies on the efficiency of the public sector has been increasingly present in academic papers. The concepts relating to public spending efficiency stand out in this scenario, because they relate to approaches to the correct allocation of public resources and economic and social development of society. A major challenge of public management is about balancing the scope of public expenditure and the results achieved with the application of these. When we think in this situation at the municipal level, one can find an even greater imbalance between spending and the impacts on society. Given the importance and representation in the national scenario of public spending, this work proposes assess the level of public spending efficiency of the municipalities of micro-region of Varginha. The methodology used is the stochastic frontier analysis, which is an estimated optimal production boundary feature using the regression multiple variables from a data set of selected production units, in which the inputs are set as independent variables and the product, is set as dependent variable. It were used as variables: Performance Indicators Aggregates (DSP’s) by areas health, sanitation, education and culture, public expenditure in health, sanitation, education and culture and the proportion of these expenditures to total expenditures of municipalities, number of inhabitants, GDP (Gross National Product)per capita, urbanization rate, and expenses whit personnel. From the analyzes, it was observed, by standard deviations, that the values ​​of DSP 's not differ from the average of the micro-region. Stochastic frontier model showed that the variables thats represents the absolute spending and GDP negatively influence the DSP's. However, population variables, the number of inhabitants and the city's urbanization rate showed a directly proportional result. The results show that spending by municipalities are not necessarily being directed to obtain the best results, or are not being applied effectively. It is hoped that the study may represent a theoretical and practical advances in the public finances field in order to enable improvement in driving the use of public resources by city managers, allowing to contribute concretely to the economic and social development of the local public administration.